Obiettivo acqua. Educazione, etica e valori alla base dello sviluppo sostenibile - Eleonora Sparano (Culture e Studi del Sociale)
Among the objectives of the paper there is the need to show that the sdgs for 2030 are strongly interrelated and that, at least for water, perhaps owing to the universal character of the resource, they need to be addressed with an integrated systemic approach. For this reason, we want to highlight the cultural value of water, as this is considered a fundamental step towards sustainable development. The text presents a review of the data on the main issues related to Objective 6, with a view to providing a broad and detailed picture of this phenomenon. The aim is to provide useful elements for the reasoning that the social sciences have to perform in their role in the face of the challenges of time. Therefore, some key concepts to be implemented in sociology will be indicated, as well as some indications of method, within a theoretical framework that refers to deep Eco-humanism and to the roots of planetary cosmopolitanism.